Internal architecture of mixed sand-and-gravel beach ridges: Miquelon-Langlade Barrier, NW Atlantic - Billy, Julie; Robin, Nicolas; Hein, Christopher J.; Certain, Raphaël; FitzGerald, Duncan M. (Marine Geology, 2014)
International audience The internal architecture of a beach-ridge system can provide clues into the processes involved in its formation. Detailed investigation of the mixed sand-and-gravel beach-ridge plain on the Miquelon-Langlade Barrier (northwest Atlantic Ocean, south of Newfoundland) provides a better understanding of such sedimentary systems in terms of internal architecture, depositional processes and driving mechanisms. Investigations of this regressive paraglacial barrier included the topographic (RTK-GPS) and ground-penetrating radar (100 to 500 MHz antennae) data collection, orthophotographs and optically stimulated luminescence (OSL) dating. The Miquelon-Langlade beach-ridge plain is composed of two opposing progradational systems, reflecting contrasting eastward and westward hydrodynamic exposures. Four ridge sets, each with concave planform shapes, define the 500–1400-m wide eastward prograding plain along the sheltered eastern coast. Two ridge-sets with linear and fan-shaped planforms define the 200–500-m wide south-westward prograding plain along the energetic western coast.Beach-ridge units overlay a basal sedimentary unit that disrupted incoming wave energy and altered the planform morphology of the prograding plain. The internal architecture pattern of individual beach ridges are characterized by sigmoidal configurations with seaward-dipping beds (2.3–4.7° true dip-angles). It is proposed that these wave-built facies are deposited as beach berms, likely by fair-weather waves. The elevations of these facies are determined by the sea level elevation and the swash height of constructive waves during their formation. Beach ridges are overlain by either peat resulting from the flooding of topographically low-lying areas, or by aeolian sand deposits of varying heights and morphologies (relict foredunes).Despite the differences in wave exposure along each coast, the sedimentary composition and internal architecture of the two progradational systems are broadly similar; bed dip angles of the ...